PROBLEMATIC BEHAVIOUR IN FOSTER CARE: INSIGHTS FROM FOSTER CARERS AND CARE CENTRE STAFF IN LITHUANIA - Pivorienė, Jolanta (International Journal of Child, Youth and Family Studies, 2025)
Children’s problematic behaviour is a common issue in care that must be recognised and understood to be effectively addressed. This study explores how foster carers and care centre staff identify and manage internalising and externalising behaviour problems in children. A quantitative study was conducted in Lithuania using a questionnaire administered to 54 care centre staff and 67 foster carers. The results indicate that foster carers feel more capable of recognising problematic behaviour than care centre staff do, and that staff struggle more with decision-making in cases of internalising problematic behaviour. However, staff feel more capable of directly helping children than supporting foster carers. While foster carers can seek additional help for children, they are less likely to do so for themselves, despite knowing where to find it. The study highlights the need to strengthen staff’s ability to identify internalising behaviour, support foster carers, and determine necessary interventions. Additionally, foster carers should be encouraged to seek help for themselves when managing children’s behavioural challenges. It is anticipated that attention to these areas would enhance care quality and caregiver well-being.